What are junior doctors for? The work of Foundation doctors in the UK: a mixed methods study. Issue 4 (8th April 2019) - Vance, Gillian; Jandial, Sharmila; Scott, Jon; Burford, Bryan
Abstract : Objectives: To examine what activities constitute the work of Foundation doctors and understand the factors that determine how that work is constructed. Design: Cross-sectional mixed methods study. Questionnaire survey of the frequency with which activities specified in curricular documents are performed. Semistructured interviews and focus groups. Setting: Postgraduate medical training in the UK. Participants: Doctors in their first 2 years of postgraduate practice (Foundation Programme). Staff who work with Foundation doctors—supervisors, nurses and employers (clinical; non-clinical). Results: Survey data from 3697 Foundation doctors identified curricular activities (41/103, 42%) that are carried out routinely (performed at least once or twice per week by >75% of respondents). However, another 30 activities (29%) were carried out rarely (at least once or twice per week by <25% respondents), largely because they are routinely part of nurses', and not doctors', work. Junior doctors indicated their work constituted three roles: 'support' of ward and team, 'independent practitioner' and 'learner'. The support function dominated work, but conflicted with stereotyped expectations of what 'being a doctor' would be. It was, however, valued by the other staff groups. The learner role was felt to be incidental to practice, but was couched in a limited definition of learning that related to new skills, rather than consolidation and practice. Activities and perceived role were shaped by the organisational context, medical hierarchies and through relationships with nurses, which could change unpredictably and cause tension. Training progression did not affect what activities were done, but supported greater autonomy in how they were carried out. Conclusions: New doctors must be fit for multiple roles. Strategies for transition should manage graduates' expectations of real-world work, and encourage teams and organisations to better accommodate graduates. These strategies may help ensure that new doctors can adapt to the variable demands of the evolving multiprofessional workforce.